2x2 - 30x - 152 = 0 simplify
x2 - 15x - 76 = 0 since -76 = -19 x 4 and -19 + 4 = -15, we have
(x + 4)(x - 19) = 0
x + 4 = 0 or x - 19 = 0
x = -4 or x = 19
x squared -2x-3 equals 0 is the same as (x + 1)(x - 3) = 0
63828
Yes it is and well done.
(2x-4)(x-1) = 0
3x2 + 2x - 8 = 0 is a quadratic equation.
x squared -2x-3 equals 0 is the same as (x + 1)(x - 3) = 0
63828
Yes it is and well done.
(2x-4)(x-1) = 0
3x2 + 2x - 8 = 0 is a quadratic equation.
If: x2+2x-3 = 0 Then: x = 1 or x = -3
3x(2x + 1)
It is a quadratic equation.
x = -1 OR x = 3
2x -2 squared = 0
1 +/- the square root of 3
x2 + 2x - 15 = 0(x + 5) (x - 3) = 0x = -5x = +3